Short-term effects of extreme air pollutant concentrations on coronary heart disease hospitalization in Henan province: a time-stratified case-crossover study - Liu, Shuming; Wang, Yongbin; Wang, Lujie; Li, Xuefang; Fei, Menghui; Dong, Pingshuan; Yang, Kan; Liu, Hui; Xie, Na; Chen, Hengwen; Chen, Guang; Li, Huan; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCoronary heart disease (CHD) is a leading cause of cardiovascular mortality, with air pollution serving as a significant risk factor. Henan Province, characterized by both a high incidence of CHD and severe air pollution, faces substantial health and economic challenges. However, limited research has explored the relationship between air pollution and CHD in this region.MethodsThis study employs a case-crossover design combined with a distributed lag non-linear model (DLNM) to examine the short-term effects of extreme concentrations of air pollutants (PM₂.₅, PM₁₀, NO₂, SO₂, CO, and O₃) on CHD hospitalizations in Henan. Data on 133,294 confirmed CHD patients from seven large hospitals across five cities (2016–2021) were collected, with patients' addresses linked to nearby air quality monitoring stations to assess exposure to air pollutants and meteorological factors. The time-stratified case-crossover design and DLNM were used to calculate relative risks (RRs) for pollutant exposure on CHD hospitalizations, and subgroup analyses were conducted to identify sensitive groups.ResultsSignificant increases in CHD hospitalizations were associated with extremely high concentrations of NO₂, SO₂, and PM₁₀, with maximum RRs of 1.768 for NO₂, 2.821 for SO₂, and 1.728 for PM₁₀ on the 7th cumulative day, while high O₃ levels showed a protective effect. Younger individuals (≤64y) and males were more sensitive to these effects, and high CO concentrations only increase the risk of CHD incidence in the younger (≤64y) subgroup. Synergistic interactions were observed between certain pollutants, such as CO and NO₂/SO₂/PM₁₀, suggesting that the negative impact of CO on CHD is amplified in a multi-pollutant environment due to interactions with other pollutants.DiscussionThese findings highlight the significant public health impact of air pollution on CHD in Henan Province.